Mengurai Batasan Aurat Wanita dalam Keluarga Perspektif Hukum Islam - Ipandang Ipandang (IAI Darussalam, 2020)
This paper aims to parse the boundaries of women's genitals in the family from Islamic law, but what is used as a framework for this analysis is M. Quraish Shihab's thoughts. In the Islamic Shari'at, it is obligatory for Muslim men and women to wear clothes that cover their genitals and are polite. The scholars agreed on the obligation to cover the genitals, however, it is different about the limits of the genitals of Muslim women. At this time, male lust arises regardless of clothes, it could be that Muslim women who wear syar'i clothes can be targeted. If Muslim women have closed their genitals, men have to lower their gaze. This paper is devoted to discussing the limits of aurat Muslim women in the family and the public as well as discussions regarding it. From the analysis that has been carried out, Muslim women in the family do not need a veil or veil with a non-mahram, it is only specific to Ummul Mu'minin. Whereas in the public sphere it is recommended to wear the headscarf for philosophical, security, and economic reasons. From the Quraish, there are three limitations to the hijab, namely, philosophical, security, and economic and that is following maqashid shari'ah.